Pig-L mediates virulence, biofilm formation, and oxidative stress tolerance in Clostridioides difficile - Cheng, Yumei; Hu, Huilin; Huang, Tingyu; Luo, Xiang; Chen, Fahui; Shi, Peng; Ma, Weihao; Lu, Yingjun; Lan, Siyu; Cui, Guzhen; Qi, Xiaolan; Liu, Ya-Jun; et al. (Frontiers in Microbiology, 2025)
BackgroundClostridioides difficile infection (CDI) represents a significant global public health concern. The Phosphatidylinositol Glycan Class L (pig-L) gene in C. difficile encodes an enzyme critical for the biosynthesis of Glycosylphosphatidylinositol (GPI) anchor, which play a vital role in bacterial surface protein localization and function.MethodsTo investigate the role of pig-L in C. difficile pathogenesis, we utilized CRISPR-Cas9 gene editing to generate a pig-L knockout strain and a complementation strain in the wild-type (WT) background. Phenotypic characterization of these strains was performed through a suite of assays, including virulence assays, biofilm formation assays, oxidative stress sensitivity testing, and antimicrobial susceptibility testing. Proteomics analysis was conducted to identify differentially expressed proteins in the knockout strain.ResultsDeletion of the pig-L gene resulted in a significant reduction in C. difficile virulence, decreased biofilm formation, and increased susceptibility to oxidative stress. Proteomic analysis revealed significant alterations in protein expression, with 170 proteins exhibiting upregulation and 101 proteins demonstrating downregulation in the knockout strain. Complementation of the pig-L gene partially restored the phenotypes observed in the deletion strain.ConclusionThese findings demonstrate that the pig-L gene functions as a crucial regulator of C. difficile virulence, biofilm formation, and peroxide resistance. Targeting the pig-L gene or its downstream effectors represents a promising avenue for the development of novel therapeutic strategies to effectively control C. difficile infection.